THE CHARACTERISTICS OF IMPROVING EDUCATIONAL WORK IN THE PROCESS OF CONTINUOUS EDUCATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In this state, the methods of organizing educational work, the content of the concept of education, the improvement of educational work and the process of continuous education, forms, means, scientific tools for the improvement of educational work, and also the theoretical foundations of the organization of educational work are described.